The Effect of Nutritional Status Empowerment on the Incidence of Preeclampsia in Pregnant Women in the 3rd Trimester (Literature Review) - As-sa'diah, Dini; Solida, Adila (Jurnal Kesehatan Masyarakat Perkotaan, 2025)
Pregnancy is the period from the time the egg is fertilized until the baby is born, which usually lasts for about 280 days or nine months. Many pregnancies go well, but there are also some that may face serious problems or complications. One that can affect the occurrence of complications during pregnancy is preeclampsia. Preeclampsia is a potentially life-threatening pregnancy complication for the mother and baby. This condition is clinically characterized by the onset of gestational hypertension (high blood pressure) and proteinuria (the presence of protein in the urine) that occurs after 20 weeks of gestation. Empowerment of the nutritional status of pregnant women is believed to reduce the risk of preeclampsia. This study aims to analyze the effect of empowerment of nutritional status on the incidence of preeclampsia in pregnant women in the third trimester through a literature review. The method used is a literature review by reviewing five recent journals from sources obtained through Google Scholar, which discuss the relationship between nutritional status and preeclampsia. The results of the analysis show that increasing knowledge and empowerment through education and nutritional interventions have a positive effect on reducing the risk of preeclampsia. Several journals show a relationship between poor nutritional status and the incidence of preeclampsia, while other factors such as hypertension and an unbalanced diet also influence the risk. The recommendation from this study is the need for a holistic approach involving education, supplementation, and social support to improve the nutritional status of pregnant women, so that it can reduce the rate of preeclampsia and improve maternal and infant health.